Arquitetura de hardware para monitor de UTI segundo padrão IEEE 1451: uma prova de conceito - Pereira, Mário Wilson Paiva (2017)
This work presents the development of a hardware architecture for ICU monitors, combining design stages of embedded systems, biomedical instrumentation, intelligent sensors and the IEEE 1451 protocol. The method used defines operational requirements, system decomposition into modules, architecture definition and implementation using commercial development platforms. The entire process is based on national and international standards and protocols, seeking to design the system within the constraints of a product and validate the concept through printed circuit board prototypes. The proposed architecture establishes a network of intelligent biomedical sensors, called STIM, controlled by a central node, called NCAP. The use of this architecture provides modular, self-configuring, easy-to-maintain, plug and play sensors with standardized communication and data interface. The work also describes the process of creating electronic data sheets of the STIMs, called TEDS, which contain the operation characteristics of each smart sensor.